Illuminating the Shadows: Sociopolitical and Counseling Needs of Undocumented Mexican Immigrants - Hipolito-Delgado, Carlos; Mann, Jolee (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2013)
<span style="line-height: 115%; font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: Calibri; mso-bidi-font-size: 11.0pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Although undocumented Mexican immigrants live in the shadows of U.S. society, they represent a growing demographic with unique sociopolitical and counseling needs. Due to limited educational achievement, limited economic opportunity, discrimination, and exclusionary policies, undocumented Mexican immigrants live a marginalized existence. Additionally, acculturative stress, changing gender roles, and fear of deportation negatively impact the psychological well-being of undocumented Mexican immigrants. Fortunately, community outreach, rapport building strategies, psycho-educational groups, and brief solution therapy have demonstrated success when working with this community. This article aims to inform counselors and psychologists about the sociopolitical conditions faced by undocumented Mexican immigrants, to explore the mental health needs that result from these conditions, and to propose interventions to address these needs.